Ekologi Integral dalam Aktivitas Menganyam Noken - Margareta Florida Kayaman; Abika Lengka; Gabriela Unane Kayaman Wakum; Florentina Lartutul; Aloysia Diana Sedik (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. Integral ecology is one of Pope Francis' offers through the Encyclical Laudato Si', to care for the earth that is sick due to irresponsible human activities resulting from the paradigms of androcentrism, patriarchy, and anthropocentrism. Pope Francis offers a new habitus, a vision that takes into account all aspects of the global crisis that includes human and social dimensions. This offer should be realized in the lives of people and society. The widows